2016
DOI: 10.3390/molecules21010100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Canthardin Sulfanilamides and Their Acid Anhydride Analogues via a Ring-Opening Reaction of Activated Aziridines and Their Associated Pharmacological Effects

Abstract: Abstract:The cantharidinimide derivatives, 5a-h, including sulfanilamides containing pyrimidyl, pyrazinyl, hydrogen, thiazolyl, and oxazolyl groups were synthesized.Modification of cantharidinimide by means of the reaction of activated aziridine ring opening led to the discovery of a novel class of antitumor compounds. The analogues 10i-k, 11l-n, 12o-p, and 16q-s were obtained from treating cantharidinimide 6 and analogues (7, 8, and 13) with activated aziridines, which produced a series of ring-opened product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the event, a treatment of the bis-mesylate with K-phthalimide in dimethylformamide (DMF) at ambient temperature smoothly afforded a single product (>90% yield) from this reaction, which was found to be the desired azetidine 39 with all-cis stereochemistry (Scheme 5). 16 The isolation of 39 as a crystalline solid could be induced by a direct addition of water to the reaction mixture. The crystallinity of 39 provided a key quality control point at this juncture of the synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the event, a treatment of the bis-mesylate with K-phthalimide in dimethylformamide (DMF) at ambient temperature smoothly afforded a single product (>90% yield) from this reaction, which was found to be the desired azetidine 39 with all-cis stereochemistry (Scheme 5). 16 The isolation of 39 as a crystalline solid could be induced by a direct addition of water to the reaction mixture. The crystallinity of 39 provided a key quality control point at this juncture of the synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other relevant derivatives are the cantharidin-sulfanil-Figure 9. Norcantharidin , cantharidin [119][120][121][122][123][124][125][126][127][128][129][130][131], and related molecules.…”
Section: Oxanorbornene Derivativesmentioning
confidence: 99%
“…The new designed analogue methyl cantharidimide (Figure 9, 9i) was effective against endocervical adenocarcinoma cell line KB-C2 overexpressing ABCB1 and against human SDHB knockout HEK-293 cell line, which overexpresses ABCG2, as well as cisplatin-resistant cells, such as KCB-4 [128]. Other relevant derivatives are the cantharidin-sulfanilamides (Figure 9, 9j) that exhibited anti-HL-60 and anti-Hep3B cell activities [129].…”
Section: Oxanorbornene Derivativesmentioning
confidence: 99%
“…In the article “Synthesis of Canthardin Sulfanilamides and Their Acid Anhydride Analogues via a Ring-Opening Reaction of Activated Aziridines and Their Associated Pharmacological Effects” [ 26 ], Mei-Hsiang Lin and coworkers reported their investigation to find new cantharidinimides and related imides containing the sulfonamide group. The modification of cantharidinimide by means of the reaction of activated aziridine ring opening led to the discovery of a novel class of antitumor compounds.…”
mentioning
confidence: 99%
“…They found that the most potent cytostatic compound, N -cantharidinimido-sulfamethazine, exhibited anti-HL-60 and anti-Hep3B cell activities. Detailed results of their investigation are presented in the article [ 26 ].…”
mentioning
confidence: 99%